2022
DOI: 10.1097/j.pain.0000000000002752
|View full text |Cite
|
Sign up to set email alerts
|

No long-term effects after a 3-week open-label placebo treatment for chronic low back pain: a 3-year follow-up of a randomized controlled trial

Abstract: Supplemental Digital Content is Available in the Text. A 3-year follow-up of 89 chronic back pain patients does not support the assumption that a 3-week open-label placebo treatment has long-term effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Many of these successful studies have also been performed as ‘open-label placebo (OLP)’ trials, wherein patients were aware of their group assignment and were informed of each placebo treatment, eliminating the ethical dilemma of using deception in clinical settings 8 9 13. OLP induced short-term outcome improvements in pain disorders such as adult and paediatric irritable bowel syndrome14–16 and other chronic pain disorders (eg, back pain, knee pain) 13 17–19. Overall, these results suggest that non-deceptive conditioned open-label placebos (COLP) may also be beneficial for head and neck cancer perioperative symptom management.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these successful studies have also been performed as ‘open-label placebo (OLP)’ trials, wherein patients were aware of their group assignment and were informed of each placebo treatment, eliminating the ethical dilemma of using deception in clinical settings 8 9 13. OLP induced short-term outcome improvements in pain disorders such as adult and paediatric irritable bowel syndrome14–16 and other chronic pain disorders (eg, back pain, knee pain) 13 17–19. Overall, these results suggest that non-deceptive conditioned open-label placebos (COLP) may also be beneficial for head and neck cancer perioperative symptom management.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the orchestration of placebo-controlled trials is a complex process (Howick, 2017), particularly in developing countries (Lepage et al, 2023;Kim et al, 2023). The success of clinical trials is influenced by diverse factors (Kupersmith and Jette, 2023;Jacobsen et al, 2023;Feldman et al, 2022), and despite the abundance of such trials, there remains a need to elucidate placebo effects in both healthy individuals and patients, particularly in studies related to the gut microbiota (Kleine-Borgmann et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…O pen-label placebo (OLP) hypoalgesia is increasingly proposed as an ethical and clinical relevant way to optimize analgesic treatment effects for a variety of populations. [1][2][3][4][5][6][7][8][9][10][11] Although effects are usually somewhat smaller for OLP than for deceptive placebo procedures, meta-analyses have concluded that there is at least a small-to-medium effect on outcomes, such as pain or other self-reported complaints (eg, distress). 2,3,11 These meta-analyses also showed that OLP procedures might work better in clinical populations than in healthy subjects.…”
mentioning
confidence: 99%
“…However, the evidence for effects on physiological or behavioral outcomes and long-term clinical outcomes is more limited. 2,3,6,8,11 More importantly, evidence varies between studies, with a large heterogeneity between study designs, populations, and outcomes. [2][3][4]7,8,11 Most of the studies in this field compared an OLP condition with a non-OLP condition within a specific patient group.…”
mentioning
confidence: 99%